Comparative study on the taxonomic relevance of gnathosomal structures in the family Zerconidae (Acari: Mesostigmata) - Ujvári, Zs. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2011)
Taxonomic relevance of hypostomal, subcapitular, epistomal and cheliceral characters within the family Zerconidaeis discussed with remarks on ontogeny, sexual-, individual- and interspecific variability of these characters. The generalstructure and chaetotaxy of the hypostome and subcapitulum is one of the most invariant among gnathosomal parts, only theshape of hypostomal, capitular and palp trochantral setae seem to have diagnostic relevance. A method is proposed fordescription of relative robustness of chelicerae. The importance of observation of subcapitular, hypostomal and cheliceralmorphology is emphasized by the example of Syskenozercon and Rotundozercon. A more careful typified system of the epistomemorphology (which was previously considered as a character of generic importance) in the known Zerconidae taxa is presented.